Retrospective analysis of clinical features and prognosis of nasopharyngeal carcinoma in children and adolescents - Gong, Tianyu; Liu, Yupeng; Jie, Huiqun; Liang, Min; Wu, Wenjin; Lu, Jingrong (Frontiers in Pediatrics, 2022)
Objectives: To investigate the clinical characteristics and prognosis of nasopharyngeal carcinoma (NPC) in children and adolescents in different age groups. Materials and Methods: The clinical data of 51 patients with NPC aged ≤18 years who were treated in Xinhua Hospital Affiliated to Shanghai Jiao Tong University School of Medicine from January 2012 to May 2017 were retrospectively analyzed. The patients were divided into children group (≤12 years old) and adolescent group (12 years old to 18 years old) with 12 years old as the boundary. The clinical characteristics, diagnosis, treatment and prognosis of the children and adolescent groups were compared. Results: The symptoms of the first diagnosis in the children group were mainly nasal congestion (P=0.043) and ear symptoms (P=0.008). The diagnosis rate of nasopharyngeal biopsy in the children group was lower (P=0.001), while the rate of diagnosis of cervical mass biopsy was significantly higher than that in the adolescent group (P=0.009). The proportion of keratinizing squamous cell carcinoma of the children group was higher than that of the adolescent group (P=0.006). There was no significant difference in TNM stage and risk stratification between the two groups, but the number of cases in the III-IVa children group who received induction chemotherapy + concurrent chemoradiotherapy was less than that in the adolescent group (P=0.013). The proportion of radiotherapy in the upper and lower cervical lymph node drainage areas was lower than that in the adolescent group (P=0.001). The percentage of recurrence and metastasis in the children group was higher than that in the adolescent group (P=0.026). Conclusion: The diagnosis in the children group depended on endoscopic biopsy and neck mass biopsy, and the proportion of keratinizing squamous cell carcinoma was higher. The number of cases of induction chemotherapy and concurrent chemoradiotherapy in the children group was less than that in the adolescent group, and the proportion of radiotherapy in the upper and lower cervical lymph node drainage areas was lower than that in the adolescent group. Clinically, it is necessary to improve the understanding of the clinical characteristics of children with NPC and take appropriate treatment strategies.